2000
DOI: 10.1002/1097-0185(20001101)260:3<213::aid-ar10>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and death in the gastric epithelium of developing rats after glucocorticoid treatments

Abstract: Glucocorticoids take part in the intense morphofunctional modifications that occur in the gastric mucosa during fetal and postnatal development. Two studies were designed to evaluate corticoids role in gastric cell proliferation and apoptosis in developing rats: in vivo, using suckling animals; in vitro, using gastric explants obtained from 20-day fetuses. These explants were cultured in DMEM/F12 medium treated or not with 50 ng/ml of corticosterone; after 22 hr, vincristine was added to the medium for 2 hr to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…GC was found to be involved in physiological activities of the gastric mucosa. For instance, Gama et al treated rats in vivo and the cultured rat gastric tissue in vitro with GC, and the results showed decreased gastric epithelial cell proliferation as well as increased cell apoptosis (16). It was also found that GC could regulate the expression of MUC5AC mRNA, which directly inhibits the synthesis of epithelial mucus layer (17).…”
Section: Discussionmentioning
confidence: 99%
“…GC was found to be involved in physiological activities of the gastric mucosa. For instance, Gama et al treated rats in vivo and the cultured rat gastric tissue in vitro with GC, and the results showed decreased gastric epithelial cell proliferation as well as increased cell apoptosis (16). It was also found that GC could regulate the expression of MUC5AC mRNA, which directly inhibits the synthesis of epithelial mucus layer (17).…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding maintenance is essential to growth (Lin et al, 1998 ; Tang et al, 1999 ; Gama et al, 2000 ; Marion et al, 2005 ; de Andrade Sá et al, 2008 ; Osaki et al, 2010 ; Rogier et al, 2014 ; Bittar et al, 2016 ; Zulian et al, 2017 ), and its premature interruption can affect gastric development; we had two main goals in this study: (1) to evaluate whether the proliferative stimulus of early weaning would be lifelong detected and how it would be associated with the distribution of dividing cells in the gland, and (2) to identify the molecules of TGFβ cascade and cell cycle response and their behavior in the gastric mucosa after breastfeeding interruption.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of hydrocortisone reduced the proliferation of the gastric epithelium in rat fetuses and pups. This was associated with increased apoptosis as measured by the TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) assay (Gama, Goldfeder, De Moraes, & Alvares, 2000). In another study (Nittoh et al, 1998), five types of glucocorticoids were tested for their effects on the viability of eosinophils and neutrophils.…”
mentioning
confidence: 99%